Evaluation of the effectiveness of the activities of non-state pension funds in Russia - Poltoryhina, Svetlana V.; Garipova, Venera V. (Journal of the Belarusian State University. Economics, 2019)
Non-state pension funds occupy a special place in the modern financial system of Russia. A brief description of the activities and performance of non-state pension funds is given. The purpose of the research is to analyze the effectiveness of non-state pension funds in Russia. The results of the work indicate the following regularities: no more than 0,35 % of the pension savings received are annually directed to the payment of the funded pension, and about 5 % of the contributions received under non-state pension insurance contracts are directed to the pensions of non-state pension funds; about 90 % of all pension payments of non-state pension funds are accounted for the payment of pensions under compulsory pension insurance; the funded pension receives no more than 25,5 % of the recipients of the pension from the number of clients. The results of the study can be used as recommendations for financial regulation of social and economic processes.
Keywords: non-state pension funds; pension system; pension reform; pension; inflation